Unemployment and Violent Extremism : Evidence from Daesh Foreign Recruits - Abdel Jelil, Mohamed; Bhatia, Kartika; Brockmeyer, Anne; Do, Quy-Toan; Joubert, Clement (World Bank, Washington, DC, 2018)
Transnational terrorist organizations such as the Islamic State group (also known as ISIS/ISIL or Daesh) have shown an ability to attract radicalized individuals from many countries to join their ranks. Using a novel data set that reports countries of residence and educational levels of a large sample of Daesh's foreign recruits, this paper finds that a lack of economic opportunities -- measured by unemployment rates disaggregated by country and education level -- explains foreign enrollment in the terrorist organization, especially for countries that are geographically closer to the Syrian Arab Republic.